The correlation between nursing workload and bloodstream infection from central venous catheter in ICU - Michali, Olga; Argyriou, Georgios; Xristopoulou, Georgia; Kapadohos, Theodore; Vasilopoulos, Georgios; Marvaki, Christina (Health & Research Journal, 2019)
Introduction: Bloodstream infection associated with the presence of central venous catheters is the second most common hospital infection in the Intensive Care Unit (ICU). The nursing stuff is an essential part of the human resources of the ICU which contributes substantially to provide holistic and effective care to critically ill patients. The level of the nursing workload and its possible influence on the clinical course and outcome of critically ill ICU patients has been systematically studied in recent years. Mainly, was studied the connection with the care quality indicators such as mortality and infections Aim: The purpose of this study was to estimate the nursing workload in the ICU and to investigate the impact of bloodstream infection from Central Venous Catheter (CLABSI). Methods: The study sample consisted of 39 patients who were hospitalized in a multidisciplinary ICU in a 3 month period. For the detection of bloodstream infections we used the surveillance definition of CDC/NHSN for in vitro confirmed bloodstream infection (CLABSI). Measurement of nursing workload was via the NAS scale and the calculation was performed for each patient once existed or entering the ICU from baseline and constantly on a daily basis. A comparison of the quantitative variables was done with the statistical criterion Pearson’s x 2 , to compare the bisectors qualitative variables selected quantitative variables was used the t-test analysis and MannWhitney test. Results: Of the total sample, 74,4% (n = 29) were male, with a mean age 59 ± 21 years. The duration of ICU stay was 24 ± 23 days and mortality was 41%. The duration of hospitalization was 28 ± 24 days and the corresponding mortality of 46.2%. All correlations presented no statistically significant difference than the first day’s NAS in which appears the biggest difference between the values (p=0,046) but the NAS of the patients who did not develop bacteremia be more increased over those experienced. Conclusions: The nursing workload in our study did not prove as a risk factor for the occurrence of bloodstream infection in the ICU.